2022
DOI: 10.1021/acs.orglett.2c00968
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-Catalyzed Atroposelective C–H Arylation of (Hetero)Arenes Using Carbene Precursors as Arylating Reagents

Abstract: Rhodium(III)-catalyzed C−H activation-based arylation of sterically hindered (hetero)arenes has been realized using diazo compounds and triazoles as arylating reagents for atroposelective synthesis of two classes of biaryls. The coupling of 3substituted indoles and N-sulfonyltriazoles afforded indoles with a C(2)−C chiral axis, while the arylation of 1-naphthylthioether with ortho-quinone diazide afforded chiral binaphthyls. These coupling systems proceeded under mild conditions via C−H activation and carbene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…Then, using CD 3 OD (10 eq) as a deuterated reagent, a deuterium experiment was carried out in the absence of 2 a under the standard conditions., The result showed that the ortho C−H bond of aniline 1 a was deuterated less than 5% after 24 h. The D/H exchange experiment was also performed under standard conditions without 2 a , with the ortho C−H bonds at 68% D and 67% D, respectively, before and after the reaction. This confirmed that the ortho C−H bond is not easily activated again [20a,21] (Scheme 3d).…”
Section: Figuresupporting
confidence: 62%
“…Then, using CD 3 OD (10 eq) as a deuterated reagent, a deuterium experiment was carried out in the absence of 2 a under the standard conditions., The result showed that the ortho C−H bond of aniline 1 a was deuterated less than 5% after 24 h. The D/H exchange experiment was also performed under standard conditions without 2 a , with the ortho C−H bonds at 68% D and 67% D, respectively, before and after the reaction. This confirmed that the ortho C−H bond is not easily activated again [20a,21] (Scheme 3d).…”
Section: Figuresupporting
confidence: 62%
“…After that, through the use of different carbene precursors, several specific rearrangement reactions of 2-oxypyridines have been realized . Because 1-diazonaphthoquinones have been utilized as the electronic reaction partners in the arylation of amides and in the atroposelective synthesis of biaryls by the groups of Antonchick and Waldmann, Cramer, Li, You and our own group, we envisioned that 1-diazonaphthoquinones could be good arylation reagents in the synthesis of N -arylated pyridones by reacting with 2-oxypyridines. The reaction might proceed through the formation of quinoid carbene intermediates, which then generates zwitterionic rhodium species.…”
mentioning
confidence: 99%
“…By employing indoles bearing a N-directing group and diazo compounds as arylating reagents, Antonchick, Waldmann and co-workers realized the synthesis of axially chiral C2-arylindoles via Rh­(III)-catalyzed C–H coupling reaction between indoles and 1-diazonaphthoquinones . The groups of Li and You also reported their own Rh­(III)-catalyzed asymmetric C–H arylation reactions to reach such biaryl atropisomers. Using indoles bearing a C3-directing group, Ackermann, Wencel-Delord and co-workers recently reported a cobalt-catalyzed enantioselective C–H arylation to generate C2-arylated indole atropisomers (Scheme c) .…”
mentioning
confidence: 99%